Orthodontic-surgical correction with a bilateral mandibular ramus sagittal osteotomy of a skeletal Class III maloclussion - Sánchez Rodríguez, María Fernanda (Revista Mexicana de Ortodoncia, 2016)
A case of a male patient of 19 years 3 months of age is reported. The chief complaint was having discomfort in the jaw. The diagnosis was a hyperdivergent skeletal class III, bilateral molar and canine class III with proclined upper incisors, bilateral anterior and posterior cross-bite, upper and lower crowding with a lower dental midline deviation. The patient also had a maxillary collapse. The patient did not refer any habit. Treatment was conducted in three phases: a pre-surgical phase: alignment, leveling, dental decompensation, tripodism (occlusal stability), transverse expansion. Surgical Phase: Mandibular LeFort I Surgery: 5mm advancement. Post-surgical phase: Detailing, retention. Active treatment time was 4 years 4 months. Removable upper and lower Hawley retainers and fi xed canine to canine both in the upper and lower arch were used. Treatment outcome was successful, obtaining bilateral canine and molar Class I, normal overjet and overbite, coincident midlines, adequate intercuspation and a harmonic facial profi le. Key words: Anterior and posterior crossbite, mandibular advancement.